Comprehensive assessment of executive functioning following childhood severe traumatic brain injury: clinical utility of the child executive functions battery - Chevignard, Mathilde; Guerra, Amanda; Fliss, Rafika; Salah, Lucie; Pineau, Emmanuelle; Notteghem, Pauline; Roche, Jeanne; Huon, Caroline; Krasny Pacini, Agata; Le Gall, Didier; Fournet, Nathalie; Roulin, Jean-Luc; et al. (Frontiers in Psychology, 2023)
Objectives To perform a detailed description of executive functioning following moderate-to-severe childhood traumatic brain injury (TBI), and to study demographic and severity factors influencing outcome. Methods A convenience sample of children/adolescents aged 7–16 years, referred to a rehabilitation department after a TBI (n = 43), was compared to normative data using a newly developed neuropsychological test battery (Child Executive Functions Battery—CEF-B) and the BRIEF. Results Performance in the TBI group was significantly impaired in most of the CEF-B subtests, with moderate to large effect sizes. Regarding everyday life, patients were significantly impaired in most BRIEF clinical scales, either in parent or in teacher reports. Univariate correlations in the TBI group did not yield significant correlations between the CEF-B and socio-economic status, TBI severity, age at injury, or time since injury. Conclusion Executive functioning is severely altered following moderate-to-severe childhood TBI and is best assessed using a combination of developmentally appropriate neuropsychological tests and behavioral ratings to provide a comprehensive understanding of children’s executive functions.